Captain Aquatica's awesome ocean - Cramp, Jess; Smith, Grace Hill; Levit, Joseph (Science superheroes., 2019)
Follows the superhero Captain Aquatica through the ocean to explore biodiversity and the importance of conservation in the ecosystem. Contains information on oceanic wildlife, specifically sharks, and highlights conservation stories. Also contains color photographs.